Developing a module for producing multimedia content for scientific research - Mohamed, Shafizan; Yusoh, Mohd Helmi; Wan Mohd Ghazali, Wan Norshira (2020)
With the increasing demands for researches to make their their discoveries known as well as commercialiazing them, it is undeniable that researches today need to find ways to better communicate their research to the public and related stakeholders. Multimedia content such as video offers researchers a dynamic way to communicate scientific concepts that are usually alien and distant to the general public. With the rise of mobile devices and a generation that expects concise online visual content, the demand for all kinds of media is booming. YouTube for example, boasts more than 1 billion users, who collectively watch about 1 billion hours of video per day, according to the company’s website. As such the internet offers the best platform for scientists to reach the audiences that will ultimately benefit from their scientific works. Unfortunately, scientists are usually not content makers, they are unable to tap into the opportunities that the online platforms can offer. As such many interesting and undoubtedly significant scientific discoveries are left on the shelves waiting to be discovered. Therefore this study aims to identify the best and most productive ways to produce multimedia contents out of scientific research. By uncovering the best and most effective methods, the study will develop a guide and module that could help scientific researches produce media content and participate in the competitive area of research commercialization.